The Impact of Interculture-Based Language Learning on English Paragraph Writing Skill in Higher Education: A Systematic Review - Ilham, Ilham (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is a systematic literature review aimed at evaluating the effectiveness of Intercultural Learning (IBL) in improving English paragraph writing skills in higher education. IBL is recognized as a pedagogical approach that integrates linguistic, cognitive, and social aspects, supporting students in understanding cultural contexts when writing. This review analyzed 25 studies published between 2016 and 2025, focusing on the application of IBL in improving writing skills for students learning English as a foreign language (EFL). Research findings indicate that IBL significantly improves students' writing quality, particularly in terms of text structure, cohesion, and coherence. Additionally, this approach helps students develop higher cultural awareness and intercultural communication skills. However, the main challenges faced in implementing IBL include time constraints, teacher readiness, and skill gaps among students. This study emphasizes the importance of institutional support and adaptive learning strategies to maximize the effectiveness of IBL. Thus, IBL can be implemented sustainably to optimize the development of students' writing skills in the context of an increasingly global higher education system.